MELURUSKAN PEMAHAMAN ADMINISTRASI - Dann Sugandha (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2005)
The Dutch and the British colonials introduced the terms ‘administratie’ and‘administration’ - the modern thought of governmental activities to gain effectiveness and efficiency. These new arts have influenced the way some Indonesian rulers rule the country. However, up to now, those terms still mean differently to different people. Some said that administratie is narrower than administration. It is merely clerical works compared to administration as a whole process of people working together to achieve certain goals. However, it is not totally true. For a better understanding of administration, first of all, we should define an organization as a system consisting a set of elements interrelated to each other. The elements consist of people, visions, objectives, missions, tasks and functions, authorities, structures, relationships, formalities, resources, and processes called administration. In this case, administration is considered as a part of the organization administrative process functioning as a tool of the organization to achieve the stated objectives. The administrative process of the organization consists of three sub-processes: (1) a process of administering or managing implemented by administrators, (2) a technical operational process conducted by operational or line workers, and (3) a process of administrative services implemented by staff workers. Those three elements are interrelated as a set of system. Managing or administering does not only consist of five elements of planning, organizing, commanding, coordinating, and controlling as Fayol stated. It is more complicated. If calculated, there are more than 50 functions of management. The author has defined administration as an overall process of the organization consisting of determining and achieving objectives by using available resources efficiently with and through other people. Management is coordinating people through P.E.O.P.L.E toward desired objectives. P.E.O.P.L.E stands for Policy making and Planning, Estimating, Organizing, Persuading, Leading, Evaluating and Controlling. In this case, controlling is the prerequisite for evaluating.